(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, Hamad His servants, the grateful, praise, and praise be to God, blessings and peace be upon our best character, our honorable Prophet One of the important topics that the Holy Qur’an includes and which cares a great interest in it is the subject of the life of the world and its adornment, therefore we must clarify what are the pests and motives for the love of the world, and know the concept and dimensions of that life and its types, as well as how between God Almighty to us decorated that life and decorate it and its fleeting baggage that does not last It is a test and exam house. Whoever passes that test wins the eternal bliss and eternal happiness, and whoever prefers that to a life and adornment, he loses the hereafter and tortures him severely. He used the Qur’anic verses, the noble prophetic hadiths and sources of interpretation in explaining that importance, as he showed them in that research, which is over a third of Investigation and the Th definition and minimum adornments of life and Anuaha and how the Department of the Koran that life as well as what are the chatter received by the difference between the world and the Hereafter